Analysis of genetic variation in mitochondrial cytochrome c oxidase subunit 1 between Haemadipsa japonica in Japan and land leeches worldwide. Issue 1 (2nd January 2019) - Sato, Naoe; Yokoyama, Chikako; Inukai, Miki; Miyashita, Saeko; Nagase, Keito; Nakano, Takafumi; Iuchi, Katsuya; Hisatomi, Hisashi
Abstract: Haemadipsa japonica is the most common land leech species found in Japan. It has been considered to possess genetic variation that limits its habitat range. In the present study, to characterize variation in the mitochondrial cytochrome c oxidase subunit 1 (cox1) gene of H. japonica specimens from various locations in Japan, we examined nucleotide sequences of the mitochondrial cox1 gene. We performed PCR of mitochondrial cox1 using 10 H. japonica specimens and compared the result with those of land leeches from around the world using a maximum likelihood (ML) tree. ML tree of H. japonica in Japan showed significant differences between cox1 sequences of specimens from Yakushima and other regions of Japan. ML tree of land leeches from around the world revealed that H. japonica had the closest relationship with H. picta from Borneo.